Going Native: Indexing Architecture of eXist-db_ An Open Source Native XML Database System - Raghad, Yaseen Lazim; Adzhar, Kamaludin (IEEE, 2013)

(untitled)
XML is a markup language specifically designed for the Internet, and it has become the standard for represent and exchange the data on the Internet due to the ease of processing the exchanged information. However, the challenge is to serve and access XML data within the database efficiently. The difference between the nature of the database structure and XML data structure became an important research topic, and this led to emergence eXist-db, a native XML database which designed specifically to store large sizes of XML documents. This paper presents the indexing architecture of eXist-db, a native XML database and modified the query engine of eXist by indexing schema supports quick identification of structural node relationships thereby enhances query process.